Assessment of the turkey’s electric power policies in terms of sustainability - (:unkn) unknown (My University, 2014)
This study, using statistical data published by the Turkish Electricity Transmission Company, analyzes key parameters such as installed capacity and energy demand growth rates, investment plans and emission rates, taking into consideration the expected increase in use through the year 2023. The results of the analyses were compared to relevant data from around the world. The weight of domestic - and especially renewable - resources in investment plans for the next 10 years was discussed. Recommendations for an investment plan to support sustainable development in Turkey are listed. Consequently, the lack of investment in domestic and renewable energy projects decreases the competitive power of Turkey vis-?-vis Organisation for Economic Co-Operation and Development countries in terms of many parameters. For a sustainable development, the country must make significant changes in its foreign-dependent energy production policies. Any future policies must encourage supplying local resources to meet the continuously increasing demand. Qualifications for incentive mechanisms applied to investments in renewable energy should be developed. The impact of the private sector on the installation of new plants must also be increased by quickly completing the privatization process. , nema